Efectos de la aplicación de tres abonos orgánicos comerciales en las características agronómicas y rendimiento del cultivo de arroz (Oryza sativa l). - Zambrano Ochoa, Daira Yomira (2019)
This research was oriented in that the crops are affected due to the poor fertilization with inadequate doses that is causing great damages to the environment and to human health, the following objective was generated which is to determine the effects of the application of three fertilizers Commercial organic in agronomic characteristics and yield of rice cultivation. The work was carried out in the Santa María Manga del Cura Parish, in El Carmen Canton, Province of Manabí. A randomized complete block design with 7 treatments and 3 repetitions was used. The variables evaluated were. Plant height, number of tillers per square meter, number of spikes, grains per spikes, grain length, weight per treatment, weight of 1000 seeds, yield per hectare. The data were evaluated by the analysis of variance using the Tukey test at 5% probability, to assign the following treatments 1) Fungi organ + Nutrients (4 l ha-1), 2) Fungi organ + Nutrients (6 l ha- 1), 3) Nutri full + Nutrients (2 l ha-1), 4) Nutri full + Nutrients (3 l ha-1), 5) Allgrow (1 l ha-1), 6) Allgrow (1.5 l ha-1) and 7) Witness (Urea 200 kg ha-1) to perform the comparison of the treatments, an economic analysis was carried out on the treatments to determine the marginal utility. The results indicated that the application with the Allgrow fertilizer (1 l ha-1) registered a higher yield with values of 5284.57 kg ha-1 and better agronomic characteristics being statistically superior to the other treatments. The economic analysis determined that the Allgrow treatment with doses of 1.0 l ha-1 with a marginal cost of $ 575,78; giving as a final result a superior utility to the other treatments with 227,46 dollars. The effects of the application of organic fertilizers presented a good development of the agronomic characteristics of the crop, obtaining results above the control. It is recommended to repeat the research with other varieties of rice, and other commercial organic fertilizers that are available to producers and provide information on the benefits of using organic fertilizers in the environment. Keywords: Rice variety, organic agriculture, production